Implementation of the Quiziz Platform in Learning Islamic Fiqh of Worship for Madrasah Aliyah Students - Subhan Fathu Alam (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the implementation of the Quizizz platform in the Islamic Jurisprudence learning process among Madrasah Aliyah students, and to evaluate its impact on students' learning enthusiasm and academic achievement. The method used in this study is a descriptive qualitative approach with a literature study method, where various literature sources such as scientific journals, books, and research reports are analyzed in depth. The results show that the use of Quizizz has a positive impact in creating an interactive, fun, and competitive learning atmosphere, thereby increasing student activity and motivation. In addition, this platform has been proven to help teachers conduct learning evaluations more efficiently and measurably. As a recommendation, the use of digital media such as Quizizz needs to be continuously improved as a strategic innovation to support the understanding of the concept of Islamic Jurisprudence while addressing the challenges of Islamic education in the digital era.